Cement-augmented sacroiliac screw fixation with cannulated versus perforated screws – A biomechanical study in an osteoporotic hemipelvis model. Issue 8 (August 2018) - Hack, J.; Krüger, A.; Masaeli, A.; Aigner, R.; Ruchholtz, S.; Oberkircher, L.
Abstract: Introduction: Cement-augmentation is a well-established way to improve the stability of sacroiliac screw fixation in osteoporosis-associated fragility fractures of the posterior pelvic ring. However, to date little is known about the influence of different techniques of cement augmentation on construct stability. The aim of this study was to evaluate the primary stability of cement-augmented sacroiliac screw fixation with cannulated versus perforated screws under cyclic loading. Materials and Methods: A total of eight fresh-frozen human cadaveric hemipelvis specimens with osteoporosis were used. After generating ventral osteotomies on both sides of the sacrum, each specimen was treated using a cement-augmented cannulated screw on one side and a cement-augmented perforated screw on the other side. Afterwards, axial cyclic loading was performed. Results: No statistically significant difference was found between cannulated and perforated screws concerning maximum load (356.25 N versus 368.75 N, p = 0.749), plastic deformation (1.95 mm versus 1.43 mm, p = 0.798) and stiffness (27.04 N/mm versus 40.40 N/mm, p = 0.645). Conclusions: Considering the at least equivalent results for perforated screws, cement augmentation via perforated screws might be an interesting option in clinical practice because of potential advantages, e.g. radiological control before cement application, reduced risk of cement displacement and time saving.